2015
DOI: 10.1186/s12977-015-0200-6
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 protease cleaves the serine-threonine kinases RIPK1 and RIPK2

Abstract: BackgroundHIV-1 protease (PR) is essential for viral infectivity as it cleaves Gag and Gag-Pol polyprotein precursors during viral maturation. Recent evidence suggests that cellular proteins can also be cleaved by PR, perhaps representing an important viral strategy to counter host defense mechanisms. Receptor-interacting protein kinase 1 (RIPK1) and RIPK2 belong to a family of serine/threonine kinases with conserved domain architecture and important functions in apoptosis, necrosis and innate immunity.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 85 publications
2
48
0
Order By: Relevance
“…Besides proteolysis of HIV-1 viral proteins, PR also cleaves host cellular targets, including various cellular kinases [ 9 12 ], suggesting intimate interactions between HIV-1 PR and host cellular proteins. In fact, among all of the HIV-1 proteins, PR has been associated with the greatest number of host factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides proteolysis of HIV-1 viral proteins, PR also cleaves host cellular targets, including various cellular kinases [ 9 12 ], suggesting intimate interactions between HIV-1 PR and host cellular proteins. In fact, among all of the HIV-1 proteins, PR has been associated with the greatest number of host factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular mechanism and virologic relevance of these interactions are not fully understood at the moment, HIV-1 PR apparently induces necrotic and apoptotic cell death in CD4+ T cells and other cell types, indicating that it may, at least in part, contribute to CD4+ T cell depletion [ 13 , 14 ]. There is also an intriguing possibility that interactions between HIV-1 PR and host cellular proteins might represent another viral strategy to evade host cellular and/or immune defenses [ 12 ]. Thus, the goal of this study was to examine the possible interactions of HIV-1 PR with cellular proteins and the impacts of these interactions on cell proliferation and viability.…”
Section: Introductionmentioning
confidence: 99%
“…RIPK1 is also recruited in a protein complex composed of TRADD, FADD, and caspase-8, which depending on additional proteins recruited, can induce apoptosis or necroptosis [67]. Recently, HIV infection of primary activated CD4 + T cells was shown to downregulate RIPK-1 through HIV-1 protease [65]. RIPK-1 modification in response to human rhinovirus and Newcastle disease virus infection has also been reported [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…RIPK-1 plays a key role in the regulation of various cellular processes such as NF-κB signalling and apoptosis [64]. Moreover RIPK-1 is a target substrate for HIV protease, a viral protein that is synthesized late in the viral life cycle and inactivates RIPK1 in HIV-infected primary CD4+ T cells [65]. To determine whether RIPK1 is similarly cleaved and inactivated in HIV-infected MDMs, in vitro mock and HIV CS204 -infected MDMs for 7 days were treated with SM -LCL161 for 2 days followed by immunoprobing for RIPK-1.…”
Section: Hiv-infection Downregulates Ripk1 In Mdmsmentioning
confidence: 99%
“…In vitro experiment with the cores of another lentivirus; the equine infectious anemia virus, showed that the viral protease can cleave the nucleocapsid protein into smaller fragments [11] leading to the suggestion of an early phase role for the PR. In previous studies it was established that proteins of the viral core (CA, NC) are substrates of the viral protease in vitro [12][13][14], while other studies identified over 30 cellular proteins that could be target of the PR as summarized in Wagner et al [15]. Nevertheless, PR inhibition studies provided controversial results, some showing an inhibitory effect on the early phase [16][17][18][19], while others did not find such effect [20,21].…”
mentioning
confidence: 99%